Workers´ social protection in Argentina (Papeles, 2024)
The coverage of social contingencies has had its greatest development around a budget: registered work in a dependency relationship. This entails a contributory coverage scheme, based mainly on financing through contributions from workers and employers. In this work, we will synthesize the various coverage systems for social contingencies - old age, disability, death, illness, work accident, family responsibilities, maternity, unemployment - for registered workers, and which constitute the central structure of the public policy of protection.However, we do not fail to point out that, in a context with high rates of labor informality, a large part of the population is left out of that Social Security contributory umbrella. For this group of people, non-contributory or assistance schemes subsidiarily establish protection against social contingencies.This leads to the need to design public policies in line with the current reality, which contemplate various situations and modalities: informal work, independent work, teleworking/work 4.0, care work, migrant work/digital nomads.
Keywords: social protection; workers; registered; informal; Argentina